Désarçonner l’écriture de soi - Dominique Rabaté (Revue Italienne d'Etudes Françaises, 2019)
In Vie secrète, Quignard confesses his admiration for Montaigne, Rousseau, Stendhal and Bataille. But he does not seek to take them as models, he wants to pursue what they have tried. That is : a self-writing literally out of any self, a way to be thrown off to quote the title of the seventh volume of Dernier royaume : Les Désarçonnés.